Podocytes loose their adhesive phenotype in focal segmental glomerulosclerosis - Nagyné Kemény Éva Ilona; Mihatsch M. J.; Dürmüller U.; Gudat F. (1995)
Podocytes in focal segmental glomerulosclerosis (FSGS) show injury and focal detachment from the glomerular basement membrane (GBM). We studied by immunofluorescence and light microscopy the distribution of components involved in the integrin mediated adhesion of podocytes to the GBM in one case of recurrent idiopathic FSGS which developed in a renal transplant. Two major integrin and actin distribution patterns were observed in podocytes depending on the stage of the disease. Alpha(5) integrin subunit showed a gradual loss in early FSGS and became undetectable in advanced FSGS. Alpha(3) integrin subunit and the beta(3) subunit of the vitronectin receptor lost their polarized expression and could be detected intracellularly in early FSGS, while in advanced stage both integrin subunits were mostly basally polarized. In addition staining for alpha(3) was markedly decreased but enhanced for beta(3). Most of the podocytes in early FSGS showed significant loss of filamentous actin together with a nonpolarized distribution and a transient expression of the HAR/GP90 receptor. An altered matrix composition was also seen corresponding to the newly formed GBM. Based on these results we propose that podocytes loose their adhesive phenotype in early FSGS, which may contribute to the detachment of podocytes from the GBM.
Keywords: Klinikai orvostan; Egyéb orvostudományok